A new species of the genus Indochinamon Yeo & Ng, 2007 (Crustacea: Brachyura: Potamoidea: Potamidae) and a new country record from Northern Vietnam - Dang, Khai; Hoang, Anh Tram; Do, Cuong (Zootaxa, 2024)
A new species of freshwater crab, Indochinamon datii n. sp. is described from Xuan Son National Park, Phu Tho Province, Northern Vietnam. The new species external morphology is most similar to I. kimboiense (Dang, 1967) and I. bavi Naruse, Nguyen & Yeo, 2011. However, it can be distinguished from the other species by characters of the carapace, telson and male first gonopod. Indochinamon malipoense Zhang & Sun in Zhang, Pan, Hao & Sun, 2020 is also recorded for the first time in Vietnam.